Mitochondria-Targeted Antioxidants MitoQ and MitoTEMPO Do Not Influence BRAF-Driven Malignant Melanoma and KRAS-Driven Lung Cancer Progression in Mice - Kristell Le Gal; Clotilde Wiel; Mohamed X. Ibrahim; Marcus Henricsson; Volkan I. Sayin; Martin O. Bergo (MDPI AG, 2021)
Cancer cells produce high levels of mitochondria-associated reactive oxygen species (ROS) that can damage macromolecules, but also promote cell signaling and proliferation. Therefore, mitochondria-targeted antioxidants have been suggested to be useful in anti-cancer therapy, but no studies have convincingly addressed this question. Here, we administered the mitochondria-targeted antioxidants MitoQ and MitoTEMPO to mice with BRAF-induced malignant melanoma and KRAS-induced lung cancer, and found that these compounds had no impact on the number of primary tumors and metastases; and did not influence mitochondrial and nuclear DNA damage levels. Moreover, MitoQ and MitoTEMPO did not influence proliferation of human melanoma and lung cancer cell lines. MitoQ and its control substance dTPP, but not MitoTEMPO, increased glycolytic rates and reduced respiration in melanoma cells; whereas only dTPP produced this effect in lung cancer cells. Our results do not support the use of mitochondria-targeted antioxidants for anti-cancer monotherapy, at least not in malignant melanoma and lung cancer.